Factors Predicting Relapse in Children with First Attack Idiopathic Nephrotic Syndrome- A Hospital Based Retrospective Study (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Nephrotic Syndrome is a disease of relapse. So, it is very important to find out such children who are prone to develop frequent relapse and the predictors responsible for relapse. This retrospective study was conducted in the department of Pediatric Nephrology, Bangabandhu Sheikh Mujib Medical University, from September 2016 to August 2017.Methods: A total of 75 patients of idiopathic nephrotic syndrome (INS) with the initial attack, aged 1–18 years, were enrolled in this study. All patients were treated with prednisolone 60 mg/m2/day, single morning dose for 6 weeks, followed by 40 mg/m2 every alternate day for another 6 weeks and were analyzed and followed upfor a minimum period of six months to identify the risk factors related to relapses.Results: Among them, 50 (66.7%) were males, 25 (33.3%) were females, with a male: female ratio of 2:1. Ten (13.3%) children had no relapse, 18 (24.0%) had infrequent relapse, and 40 (53.3%) had frequent relapse. Children responding between 2 and 4 weeks after the start of treatment had a more chance of relapse (P = 0.002) than those who responded less than 1 week. Only urinary tract infection and respiratory tract infection are independent risk factors for subsequent relapse. Children with INS whohave UTI atonset had 1.55 times more chance for further relapse and RTI caused 1.42 times more chance for relapse. Patient with low serum albumin have 1.91 times more chance for relapse than with high albumin with in significant association.Conclusion: Young age at diagnosis of INS, male gender, low serum albumin and infections were predictive risk factors of multiple relapses. So, physicians should be vigilant to monitor these patients closely and counsel the families of nephrotic children regarding the prediction of subsequent relapses and ultimate outcome.J Com Med Col Teachers’ Asso July 2023; 27(2): 57-61